Is umbilical cord milking always an advantage?. (16th February 2016) - Kilicdag, Hasan; Gulcan, Hande; Hanta, Deniz; Torer, Birgin; Gokmen, Zeynel; Ozdemir, Sonay Incesoy; Antmen, Bulent Ali
Abstract: Objective : The role of cord milking as an alternative to delayed cord clamping is an area that requires more research. Purpose of this clinical trial was to investigate the impact of umbilical cord milking on the absolute neutrophil counts (ANCs) and the neutropenia frequency of preterm infants. Methods : Fifty-eight pregnant women were randomly assigned to one of the umbilical cord milking and control groups. A total of 54 preterm infants (gestational age ≤32 weeks) were enrolled into the study. The umbilical cords of 25 infants were clamped immediately after birth, and in 29 infants, umbilical cord milking was performed first. Results : The ANCs were statistically significantly lower in the cord milking group compared with the control group on days 1, 3 and 7. The frequency of neutropenia was higher in the cord milking group compared with the control group. Conclusion : In our study, ANCs were lower in the cord milking group and the frequency of neutropenia was higher. Umbilical cord milking plays a role on the ANCs of preterm infants.